Atlas of Religion in China: Social and Geographical Contexts. - Fenggang Yang (Religious Studies, Theology and Philosophy E-Books Online, Collection 2018, ISBN: 9789004353350., 2018)
The speed and the scale with which traditional religions in China have been revived and new spiritual movements have emerged in recent decades make it difficult for scholars to stay up-to-date on the religious transformations within Chinese society. This unique atlas presents a bird's-eye view of the religious landscape in China today. In more than 150 full-color maps and six different case studies, it maps the officially registered venues of China's major religions - Buddhism, Christianity (Protestant and Catholic), Daoism, and Islam - at the national, provincial, and county levels. The atlas also outlines the contours of Confucianism, folk religion, and the Mao cult. Further, it describes the main organizations, beliefs, and rituals of China's main religions, as well as the social and demographic characteristics of their respective believers. Putting multiple religions side by side in their contexts, this atlas deploys the latest qualitative, quantitative and spatial data acquired from censuses, surveys, and fieldwork to offer a definitive overview of religion in contemporary China. An essential resource for all scholars and students of religion and society in China.